RETROSPECTIVE DYNAMIC STUDY OF THE CURRENT MORBIDITY OF MEDICAL AND NON-MEDICAL SPECIALISTS IN PRE-HOSPITAL HEALTH CARE - Lidiya Hristova; Nevena Tzacheva; Rouja Nikolova; Velik Grigorov (Peytchinski Publishing, 2021)
In recent years, the healthcare system has been considered by researchers to be a high-risk area, with registered diseases above the average level compared to other economic activities. This leads to high rates of permanently reduced efficiency and premature mortality. In the present study, we looked for the determinants of negative changes in the health status of employees in pre-hospital medical care, which in addition to socio-economic, are related to the work environment and the work process. The main guidelines for really overcoming these negative trends are: occupational health activities such as creating adequate regimes of work and rest, healthy and safe working conditions, health promotion and the unifying details of the Unified Health Integrated Dossier [UHID]. This occupational medicine dossier, developed as a module of "cloud structure" of E-health in Bulgaria, allowed the study of the health status in dynamics for a retrospective period of medical and non-medical specialists in two large diagnostic counseling centers [DCC] in Varna. It was found that in the structure of momentary disease for the two DCC in the first place are diseases of the eye and its appendages - 221,74%, followed by diseases of the circulatory system -101,45% and diseases of the musculoskeletal system and connective tissue by 28,99%. UHID with occupational medicine orientation is useful both for the employers and for the control and expert structures for assessment of the health status under specific working conditions in pre-hospital medical care. The study is supported by the National Scientific Program "e-Health in Bulgaria" [2018-2020], incl. and with financial support for participation in international scientific forums.